South Meets West. - Alvim, Fernando; Bamgboyé, Oladélé Ajiboyé; Douala-Bell, Marilyn; Fibicher, Bernhard; Geers, Kendell; Gysi, Sandra; Kellner, Clive; Konaté, Yacouba; Kwami, Atta; Njami, Simon; Nkrumah, Joe; Okpe, Tonie; et al. (Accra : National Museum of Ghana, 1999)
Alexander, Jane ; Alvim, Fernando ; Gaba, Meschac ; Geers, Kendell ; Gutsa, Tapfuma ; Kwami, Atta ; Leye, Goddy ; Mthethwa, Zwelethu ; Rose, Tracey ; Shonibare, Yinka ; Tayou, Pascale Marthine ; Touré, Yacouba ; Vari, Minnette ; Zinkpe, Dominique
bibliografie
biografie
Duits
Engels
boek
Keywords: Afrika